Sucupira‑preta micropropagation through axillary buds - Moura, Luciana Coelho de; Titon, Miranda; Fernandes, José Sebastião Cunha; Santana, Reynaldo Campos; Oliveira, Marcio Leles Romarco de (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the use of growth regulators, antioxidant additives, type of explants, and coverage intensity of acclimatized seedlings in the micropropagation of sucupira‑preta (Bowdichia virgilioides) through axillary buds. Explants were cultured for multiplication on WPM medium, supplemented with concentrations of benzylaminopurine (BAP). In the elongation phase, treatments consisted of naphthaleneacetic acid (NAA) and BAP combinations added to the medium. For rooting, shoots were inoculated in medium containing concentrations of indolbutyric acid or combinations of the additives polyvinylpyrrolidone and charcoal, in different NAA concentrations. Plants were transplanted to plastic cups with substrate, and covered with polyethylene bags. Later, the bags were withdrawn, or perforated, or not withdrawn, which constituted the in vitro pre‑acclimatization treatments. Ex vitro acclimatization was carried out after the period of in vitro pre‑acclimatization. Sucupira‑preta had the best micropropagation using: cotyledon segments and 0.3 mg L-1 BAP, for multiplication; 0.3 mg L-1 NAA and 0.03 mg L-1 BAP, for elongation; and 2,0 mg L-1 activated carbon for rooting and for the in vitro pre‑acclimatization, with the use of a transparent plastic cover around seedling.